2013
DOI: 10.1007/s00423-013-1051-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of functional end-to-end esophagojejunostomy in totally laparoscopic total gastrectomy

Abstract: PurposeTotally laparoscopic total gastrectomy (TLTG) is unpopular because reconstruction is difficult. In fact, esophagojejunostomy is the most difficult surgical technique in TLTG. We adopted functional end-to-end anastomosis for esophagojejunostomy to simplify the procedure. The present study assesses the feasibility and surgical outcomes of TLTG with functional end-to-end esophagojejunostomy.MethodsWe assessed the intraoperative and postoperative outcomes of 65 consecutive patients who underwent TLTG with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
0
39
2
5
Order By: Relevance
“…This also suggested that the long-term survival for these patients may be expected to be equivalent in the two groups, although follow-up studies are needed to confirm this. Some previous studies have shown that totally laparoscopic total gastrectomy (TLTG) using either functional end-to-end esophagojejunostommy or OrVil TM reconstructions is an acceptable surgical procedure [20,21]. Blood losses and postoperative morbidities in these studies were similar to those in our study, although our operation times were longer than those in the TLTG studies.…”
Section: Discussioncontrasting
confidence: 33%
“…This also suggested that the long-term survival for these patients may be expected to be equivalent in the two groups, although follow-up studies are needed to confirm this. Some previous studies have shown that totally laparoscopic total gastrectomy (TLTG) using either functional end-to-end esophagojejunostommy or OrVil TM reconstructions is an acceptable surgical procedure [20,21]. Blood losses and postoperative morbidities in these studies were similar to those in our study, although our operation times were longer than those in the TLTG studies.…”
Section: Discussioncontrasting
confidence: 33%
“…[19][20][21][22][23][24][25][26][27][28][29] However, there were no differences in the surgical outcomes between extracorporeal and intracorporeal E-J stomy or between circular and linear stapling. The rate of E-J leakage ranged from 0% to 7.4% overall, from 1.5% to 7.4% for circular stapling, [14][15][16][17][18][19][20][21] and from 0% to 6% for linear stapling.…”
Section: Reconstruction Methodsmentioning
confidence: 68%
“…Two types of esophagojejunostomy have been reported using linear staplers, a functional end-to-end anastomosis [35][36][37][38] and a side-to-side anastomosis (or the overlap method) [39][40][41][42][43]. The functional end-to-end procedure is performed by inserting the linear stapler into the esophagus thorough a small hole on the left side of the esophageal stump and simultaneously lifting the jejunum to insert the stapler through a small hole on the opposite side of the jejunum mesenterium.…”
Section: Reconstruction Methods After Laparoscopic Total Gastrectomymentioning
confidence: 99%